A Guideline of the Application of Buddhists Doctrines for Solving Drinking Problem of Non Din Daeng People, Non Din Daeng District, Buriram Provin - Surapañño, Phra Na; Arnando, Phramaha Thanorm; Suvaco, Phramaha Phocana (Academic MCU Buriram Journal, 2024)
The purpose of this research were: 1) study the problem of drinking alcohol among the people of Non Din Daeng Subdistrict. Non Din Daeng District Buriram Province 2) Study the principles of Buddhism that solve the problem of drinking alcohol among the people of Non Din Daeng Subdistrict. Non Din Daeng District Buriram Province and 3) study the application of Buddhist principles to solve the problem of alcohol drinking among the people of Non Din Daeng Subdistrict. Non Din Daeng District Buriram Province. It is qualitative research. By studying and analyzing data from documents. and in-depth interviews Then the research results are presented using descriptive analysis. The research result found that: 1. The problem of drinking alcohol among the people of Non Din Daeng Subdistrict. Non Din Daeng District Buriram Province Most people drink because of stress, debt, and various problems in life. Some people drink because they have to socialize. As for teenagers, drinking alcohol is accepted by the group. 2. Buddhist principles that solve the problem of alcohol drinking among the people of Non Din Daeng Subdistrict. Non Din Daeng District Buriram Province includes 1) the 5th precepts, 2) Kalyanamitthamma, 3) mindfulness, 4) yonisomanasikāra, and 5) true value, false value. 3. Application of mindfulness principles That is, being conscious about drinking or not drinking. Drinking alcohol must consider the effects on family, society, culture, and the law. 4) Application of the principles of Yonisomasikāra. It is about applying ideas in the right way. Good things to do and bad things not to do. or what is beneficial and what is harmful. 5) Application of principles of true value and artificial value. Apply it by considering that intrinsic value means something useful. As for artificial value, it refers to things that are manipulated by advertisements to make people happy. If these principles are followed correctly and appropriately You can stay away from drinking alcohol and liquor.